Hard and soft tissue alterations after the application of different soft tissue grafting materials during immediate dental implant placement: a systematic review and Bayesian network meta-analysis - Ali Azadi; Fatemeh Rezaei; Atoosa Yazdani; Kimia Hejazi; Aryousha Moallem Savasari; Reza Amid; Mahdi Kadkhodazadeh (BMC Oral Health)
Abstract Background The aim of this review is to compare the clinical outcomes of different soft tissue grafting materials (connective tissue graft (CTG), platelet-rich fibrin (L-PRF), allogenic and xenogenic substitutes) applied in immediate implant placement with each other. Methods Through an electronic search regarding the study’s main question (“In patients with non-restorable teeth, who receive immediate dental implants (P), what is the best adjunctive soft tissue grafting approach among different autogenous, allogenous, and xenogenous grafts (I), to achieve the desired hard and soft tissue structure (O), compared to sites without grafting (C)?”) in PubMed, Scopus, and ISI Web of Science, randomized controlled clinical trials (RCTs) using different soft tissue grafts were identified and analyzed using a Bayesian random-effect network meta-analysis framework. The pink esthetic score (PES), marginal interproximal bone level changes (MIBL), buccal bone thickness changes (BBT), keratinized tissue width changes (KTW), soft tissue thickness changes (STT), papilla height changes (PH), midfacial gingival margin level changes (MGML) were defined as desired outcomes of the study; except for the MIBL with 12 – 24 months of follow-up, 6 – 12 months is considered for other outcomes. Results After duplication removal, 903 studies were identified through the electronic search; from which 21 RCTs were included in the review. Among all comparisons in different outcomes, only CTG demonstrated a significantly higher gain in STT compared to not placing soft tissue graft. However, CTG in MIBL, KTW, STT, PH, and MGML, and uni-layer xenogenic collagen matrix in PES were the superior treatments, according to the treatment ranking based on surface under cumulative ranking (SUCRA). Conclusions At the time of immediate implantation, there is no significant difference between different soft tissue grafts regarding the clinical outcomes of implants. However, the utilization of CTG can be suggested in cases with thin soft tissue. The acceptable efficacy of allogenic and xenogenic materials and the non-significant difference between them and CTG indicate supporting evidence for the application of these materials to specific clinical situations simultaneously with immediate implantation. Systematic review registration CRD42024568586.